2016
DOI: 10.5114/pson.2016.62055
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of mental adaptation to disease as an indicator of the quality of life in patients with lung cancer

Abstract: StreszczenieDuży wpływ na ocenę jakości życia pacjentów z rakiem płuc ma zdolność szybkiego przystosowania psychicznego do choroby nowotworowej i radzenie sobie z objawami ubocznymi chemioterapii. Przystosowanie psychiczne do choroby jest uzależnione od wielu czynników, m.in. stylu radzenia sobie ze stresem oraz poziomu odczuwanego zmęczenia. Celem badań było ustalenie związku między stylem radzenia sobie ze stresem i odczuwanym zmęczeniem a przystosowaniem psychicznym do choroby nowotworowej. Badania przeprow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The authors’ research results show that in cancer patients, strategies of fighting spirit and positive reevaluation are dominant. The study conducted by Krawczyk et al showed that patients with lung cancer are also characterized by fighting spirit (M = 23.00; SD = 3.27) and positive reevaluation (M = 21.69; SD = 2.39), while strategies of anxiety and helplessness–hopelessness achieved much lower values (respectively, M = 15.94; SD = 3.72 for anxiety and M = 12.39; SD = 3.32 for helplessness–hopelessness) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors’ research results show that in cancer patients, strategies of fighting spirit and positive reevaluation are dominant. The study conducted by Krawczyk et al showed that patients with lung cancer are also characterized by fighting spirit (M = 23.00; SD = 3.27) and positive reevaluation (M = 21.69; SD = 2.39), while strategies of anxiety and helplessness–hopelessness achieved much lower values (respectively, M = 15.94; SD = 3.72 for anxiety and M = 12.39; SD = 3.32 for helplessness–hopelessness) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%